Delayed feedback control for chatter suppression in turning machines. (November 2019) - Mancisidor, I.; Pena-Sevillano, A.; Dombovari, Z.; Barcena, R.; Munoa, J.
Abstract: The employment of active control devices has been demonstrated as one of the most effective methods to suppress chatter vibrations in machine tools. However, the commonly employed control laws are generalist and focused on the reduction of any type of vibration. The present work proposes a control law focused on the main cause of chatter vibrations. The strategy is based on a delayed feedback that distorts the regenerative effect and virtually reduces the overlap factor between successive waves. Experimental results show that the proposed law enables the suppression of chatter vibrations.